Facile fabrication of urchin-like hollow boehmite and alumina microspheres with a hierarchical structure via Triton X-100 assisted hydrothermal synthesis1. Issue 6 (14th February 2015) - Huang, Huihui; Wang, Lei; Cai, Yuan; Zhou, Caicheng; Yuan, Yuewei; Zhang, Xiaojun; Wan, Hui; Guan, Guofeng
<x xml:space="preserve">Abstract</x> Urchin-like hollow boehmite and alumina microspheres were fabricated via Triton X-100 assisted hydrothermal synthesis.